Pengaruh Intensitas Menonton Youtube Terhadap Perilaku Konsumerisme Audiens - Abyandary, Tsany Tsany (Tuturlogi: Journal of Southeast Asian Communication, 2021)
Social media intensity is one of the causes of consumerism. This research will conduct the effect  of social media intensity on consumerism, with Gaya Berkendara Youtube channel as the research  subject. Gaya Berkendara Youtube channel itself is a channel focusing on the cycling hobby. This  research will use a positivist paradigm with an explanative quantitative methodology to test the influence  of the intensity of watching Gaya Berkendara Youtube channel on consumerism habits. The population  of this research itself is 39.100 subscribers, so the sample in this research is 109 respondents chosen with  a convenience sampling method. The respondents are those who know about the Gaya Berkendara  Youtube channel and are part of subscribers. All of the data that has been gathered are tested using  simple linear regressions. The result is indicating that the intensity of watching Gaya Berkendara Youtube  channel is affecting the subscribers' consumerism habits. This research is based on the uses and  gratification theory to analyze the effect of media consumption, as individuals themselves have full control  over how they use their media. However, this research focus is on the intensity of media consumption  without any deep consideration of social media influencers. Any suggestion for future research is to  include social media influencers as a variable to know its effect separately.